REFLECTANCE VARIATIONS IN HEAT-TREATED ILVAITE - Bonazzi P.; Bindi L.; Olmi F. (My University, 2001)
Ilvaite, a black mixed-valence iron silicate, undergoes oxidation-dehydrogenation reaction when heated in air. Variations in the optical properties were investigated as function of the structural adjustments accompanying the process. Reflectance measurements were carried out in air on crystallographically oriented crystals heated at increasing temperatures (selected wavelengths of 471.1, 548.3, 586.6, and 652.3 nm). As expected on the basis of the strong structural anisotropy, sections parallel to the c axis (i.e. the chain axis) exhibit maximum bireflectance. The most relevant variation induced by heating affects the Relue which appears to increase as consequence of the shortening of the M1-M1 contact along the c axis.